APAKAH INTENSITAS PENGGUNAAN INSTAGRAM BERHUBUNGAN DENGAN KEPERCAYAAN DIRI: ANALISIS KORELASI PADA MAHASISWA BARU - Panji Candra Ramadhan; Aprillia Mega Rosdiana; Billah Ahsanul Karima (Jurnal Psikologi Malahayati, 2022)
ABSTRACT: DOES INSTAGRAM USAGE INTENSITY RELATED TO SELF CONFIDENCE: CORRELATION ANALYSYS OF COLLEGE FRESHMAN STUDENT New students tend to think positively and are confident about their ability to use Instagram social media. This study aims to determine the level of intensity of using Instagram social media, the level of self-confidence, and the relationship between the intensity of the use of social media with the confidence of freshman college studentd majoring in management at UIN Malang Class of 2021.The sample were 73 freshman who have an Instagram account and access it at least one hour per day.  The scale used to collect data is the intensity scale of Instagram social media use and the self-confidence scale. The data analysed by correlational test to determine the relationship between the intensity of social media use and self-confidence. The results of this study found that the intensity of using Instagram social media was not related to self-confidence. It means that the high and low intensity of using Instagram social media has no effect on the high and low level of student self-confidence. Keywords: College Freshman Students,  Instagram Usage Intensity, Self Confidence  Mahasiswa baru cenderung memiliki cara berpikir yang positif dan percaya diri terhadap kemampuannya dalam memanfaatkan media sosial Instagram. Penelitian ini bertujuan untuk mengetahui tingkat intensitas penggunaan media sosial Instagram, tingkat kepercayaan diri, serta hubungan antara intensitas penggunaan media sosial dengan kepercayaan diri mahasiswa baru jurusan manajemen UIN Malang Angkatan 2021. Sampel dalam penelitian ini adalah 73 mahasiswa baru yang memiliki akun instagram dan mengaksesnya minimal satu jam per hari. Skala yang digunakan untuk mengumpulkan data yakni skala intensitas penggunaan media sosial Instagram dan skala kepercayaan diri. Data dianalisis menggunakan uji korelasional untuk mengetahui hubungan antara intensitas penggunaan media sosial dan kepercayaan diri. Hasil dari penelitian ini menemukan bahwa intensitas penggunaan media sosial instagram tidak berhubungan dengan kepercayaan diri. Hal ini menunjukkan bahwa tinggi rendahnya intensitas penggunaan media sosial instagram tidak berpengaruh dengan tinggi rendahnya tingkat kepercayaan diri mahasiswa. Kata Kunci : Mahasiswa Baru, Intensitas Penggunaan Instagram, Kepercayaan Diri